Low-Frequency Spectra of Neutron Star Plus Ob Supergiant Binaries: Does Wind Density Drive Persistent and Flaring Modes of Accretion? - El Mellah, I (OXFORD UNIV PRESS, 2025)
Neutron star high-mass X-ray binaries are well studied in wavebands between the infrared and hard X-rays. Their low-frequency millimeter and radio properties, on the other hand, remain poorly understood. We present observations of the millimeter and radio emission of binaries where a neutron star accretes from an OB supergiant. We report Atacama Large Millimeter/submillimeter Array and Northern Extended Millimeter Array millimeter observations of twelve systems, supplemented by Very Large Array radio observations of six of those targets. Our targets include six Supergiant X-ray Binaries (SgXBs), four Supergiant Fast X-ray Transients (SFXTs), and two intermediate systems. Nine out of twelve targets, including all SFXTs, are detected in at least one millimeter band, while in the radio, only two targets are detected. All detected targets display inverted radio/millimeter spectra, with spectral indices in the range alpha = 0 . 6-0 . 8 for those systems where accurate spectral energy distribution (SED) fits could be performed. We conclude, first, that the low-frequency SEDs of neutron star SFXTs and SgXBs are dominated by free-free emission from the OB supergiant s stellar wind, and that jet emission is unlikely to be observed unless the systems can be detected at sub-GHz frequencies. Secondly, we find that SFXTs are fainter at 100 GHz than prototypical SgXBs, probably due to systematically less dense winds in the former, as supported further by the differences in their fluorescence Fe K alpha lines. We furthermore compare the stellar wind constraints obtained from our millimeter observations with those from IR/optical/UV studies and bow shock detections, and present evidence for long-term stellar wind variability visible in the thermal emission.